Desenvolvimento pessoal e acadêmico no ciclo básico durante a pandemia - Zambrana, Giovana Melo Chavez (Universidade Federal de São Carlos, 2025)
Introduction: This work presents a reflective autobiographical narrative about the personal and academic development of a medical student from the Federal University of São Carlos during the pre-clinical years, amid the COVID-19 pandemic. The text discusses the course methodology, the transition to remote learning, adaptation to the Emergency Remote Teaching (ENPE) format, the role of facilitators in the learning process, and the challenges of integrating theory and practice during the suspension of in-person activities. Objectives: To explore the developmental experiences of a medical student in the early years of the program, shaped by the COVID-19 pandemic, remote learning, and social isolation. Methods: The methodology consisted of the construction of self-authored narratives based on reflective portfolios developed during the pre-clinical years, combined with a literature review about active learning, the Constructivist Spiral, the COVID-19 pandemic, and medical education. Conclusion: In summary, despite the measures adopted by the program during social isolation, several learning setbacks were observed, especially in real-life settings and practical skills. However, the text also highlights the development of autonomy, resilience, and critical thinking in response to the challenges imposed by the pandemic context.
Personal and academic development in basic cycle during the pandemic
Keywords: Metodologia ativa; Ensino médico; Pandemia de COVID-19; Active learning; Medical education; COVID-19 pandemic; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 4. Educação de Qualidade